Root Cause Analysis Of Quality Control And Cost Control Of Implementing The Referback Program In First Level Health Facilities - Solida, Adila; Amir, Andy; Sari, Rumita Ena; Widiastuti, Fitri (Journal of Applied Nursing and Health, 2023)
Background: The incidence of chronic diseases in Jambi City is still high from year to year. The Referback Program (PRB) is one of the government's efforts through BPJS Health in collaboration with health facilities to ensure chronic disease sufferers have easier access to obtain the medicines they need at an efficient cost. This research aims to analyze the main problems of quality control and cost control of PRB implementation in terms of man, material-machine, method, market, money and time elements at FKTP in Jambi City. Methods: The research was conducted using qualitative methods using the perspective of Root Cause Analysis (RCA) theory to form research procedures. The informants consisted of the person in charge of PRB, the head of the community health center and PRB participants at FKTP in Jambi City. The research instrument is a structured interview sheet. Data analysis uses thematic analysis techniques according to the RCA flow Results: The research results found that the main cause of the problem was weak coordination between PRB officers and BPJS Health in implementing PRB at FKTP. Conclusion: It is recommended that BPJS Health be more active in providing outreach and special training to PRB officers as well as setting up a clear monitoring and evaluation system regarding the implementation of PRB in FKTP